Effect of intranasal oxytocin administration on psychiatric symptoms: A meta-analysis of placebo-controlled studies. Issue 3 (30th August 2015) - Hofmann, Stefan G.; Fang, Angela; Brager, Daniel N.
Abstract: Clinical trials of intranasal administration of oxytocin for treating psychiatric problems have yielded mixed results. To conduct a quantitative review of placebo-controlled clinical trials of intranasally-administered oxytocin (OT) for psychiatric symptoms, manual and electronic searches using PubMed and PsycINFO were conducted. Of 1828 entries, 16 placebo-controlled studies totaling 330 participants were included in the analysis. The overall placebo-controlled effect size was moderately strong (Hedges׳ g =0.67) and robust as suggested by the fail-safe N and funnel plot analysis. OT reduced symptoms of depression, anxiety, autism/repetitive behaviors, psychotic symptoms, and general psychopathology. In the combined sample, symptom reduction was moderated by frequency of administration. Publication year and diagnostic category did not moderate the effect of OT on the clinical outcome measures. We conclude that intranasal administration of OT is a potentially useful intervention for reducing psychiatric symptoms. However, more studies are needed to determine the best treatment target and to identify the mechanism of treatment change. Highlights: To examine the effects of oxytocin in clinical populations, we conducted a meta-analysis. Of 1828 entries, 16 placebo-controlled studies were included in the analysis. The effect size was moderately strong, but should be judged as preliminary. Further studies of oxytocin as a clinical intervention are warranted.